PERLINDUNGAN HUKUM TERHADAP ALIRAN KEPERCAYAAN BERDASARKAN PERATURAN PERUNDANG-UNDANGAN - Anthon Fathanudien; Akhmad Shodikin (IAIN Syekh Nurjati Cirebon, 2023)
The author conducted this research with the background that Based on the 1st principle of the basic state of Pancasila, Indonesia is a country that has faith in the existence of God, Therefore, religious freedom is one form of Human Rights, namely the right of human freedom to choose and embrace a religion. or beliefs that are believed to be true based on considerations of reason and conscience. The purpose of writing this paper is to find out what are the legal protection arrangements regarding the flow of belief, and to find out and analyze the laws and regulations regarding the flow of belief in Kuningan district. The method used in this research is an empirical juridical approach by strengthening primary and secondary data and data collection techniques used through observation and interviews. The result of this research is that the regulation of belief and religion based on the prevailing regulations in Indonesia is regulated by a Joint Decree which includes 3 Ministers, namely (Minister of Home Affairs, Minister of Religion, and Attorney General), Article 28 E, paragraphs 1 and 2, Article 28 I paragraph 1, Article 29 paragraph (2) of the 1945 Constitution of the Republic of Indonesia covering freedom of religion, Constitutional Court Decision Number 97/PPU-XIV Year 2016 concerning Prevention of Abuse and/or Religious Guidelines, namely Islam, Christianity, Catholicism, Hindus, Buddhists, and Confucians, regarding the change in the identity of women who are followers of the religion column of the resident's identity card, regarding the coordination team for supervising the flow of beliefs and religious sects in society. The conclusion of writing this thesis is that Kuningan has acknowledged the existence of a sect of belief and the writing or inclusion of the sect on the identity card is with the words Belief in God Almighty. And the community has also tolerated each other between religious communities